2018
DOI: 10.1097/brs.0000000000002575
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Neurophysiological Monitoring in Spine Surgery

Abstract: 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 14 publications
0
40
0
1
Order By: Relevance
“…Considering the high incidence of complications in spine surgery, during the last years several authors focused their attention on the risk factors related to the onset of complications and on predictive models of complications after spine surgery [12][13][14][15][16]. Moreover, several preventive measures have been studied and recently described in order to reduce complications in spine surgery, concerning intraoperative neuromonitoring, blood loss reduction, and infections and thrombosis prophylaxis [19][20][21][22][23]. Sethi et al [24] reported their experience concerning the application of Lean methodology in orthopedic surgery and specifically in spine surgery.…”
Section: Preventive Measures To Improve Safety: the Who Surgical Safementioning
confidence: 99%
See 1 more Smart Citation
“…Considering the high incidence of complications in spine surgery, during the last years several authors focused their attention on the risk factors related to the onset of complications and on predictive models of complications after spine surgery [12][13][14][15][16]. Moreover, several preventive measures have been studied and recently described in order to reduce complications in spine surgery, concerning intraoperative neuromonitoring, blood loss reduction, and infections and thrombosis prophylaxis [19][20][21][22][23]. Sethi et al [24] reported their experience concerning the application of Lean methodology in orthopedic surgery and specifically in spine surgery.…”
Section: Preventive Measures To Improve Safety: the Who Surgical Safementioning
confidence: 99%
“…In spinal surgery, many preventive measures were investigated to reduce complications [19][20][21][22][23][24], but there is no report on the effectiveness of the WHO checklist in reducing complications.…”
Section: Introductionmentioning
confidence: 99%
“…The overall confidence in the results of the 28 reviews was rated as “low” in 2 SRs 9 , 10 and “critically low” in the rest 11 - 36 ( Table 3 ). Critical appraisal of each SR is found in Table S2 in the supplemental material.…”
Section: Resultsmentioning
confidence: 99%
“…For intramedullary tumor resection, intraoperative electrophysiological monitoring can reduce the risk of neurological damage. [ 33 , 37 , 38 ] However, some scholars have pointed out that intraoperative monitoring may limit the scope of tumor resection. [ 39 ] The lesions may have solid and cystic components.…”
Section: Discussionmentioning
confidence: 99%